Prosthetic alignment after total knee replacement is not associated with dissatisfaction or change in Oxford Knee Score. A multivariable regression analysis - Huijbregts, H.; Khan, Riaz; Fick, Daniel; Jarrett, O.; Haebich, S. (2016)
Background: Approximately 18% of the patients are dissatisfied with the result of total knee replacement. However, the relation between dissatisfaction and prosthetic alignment has not been investigated before. Methods: We retrospectively analysed prospectively gathered data of all patients who had a primary TKR, preoperative and one-year postoperative Oxford Knee Scores (OKS) and postoperative computed tomography (CT). The CT protocol measures hip-knee-ankle (HKA) angle, and coronal, sagittal and axial component alignment. Satisfaction was defined using a five-item Likert scale. We dichotomised dissatisfaction by combining '(very) dissatisfied' and 'neutral/not sure'. Associations with dissatisfaction and change in OKS were calculated using multivariable logistic and linear regression models. Results: 230 TKRs were implanted in 105 men and 106 women. At one year, 12% were (very) dissatisfied and 10% neutral. Coronal alignment of the femoral component was 0.5 degrees more accurate in patients who were satisfied at one year. The other alignment measurements were not different between satisfied and dissatisfied patients. All radiographic measurements had a P-value > 0.10 on univariate analyses. At one year, dissatisfaction was associated with the three-months OKS. Change in OKS was associated with three-months OKS, preoperative physical SF-12, preoperative pain and cruciate retaining design. Discussion: Neither mechanical axis, nor component alignment, is associated with dissatisfaction at one year following TKR. Patients get the best outcome when pain reduction and function improvement are optimal during the first three months and when the indication to embark on surgery is based on physical limitations rather than on a high pain score. Level of evidence: 2.